2003
DOI: 10.1001/archotol.129.12.1340
|View full text |Cite
|
Sign up to set email alerts
|

Gorham Stout Syndrome (Disappearing Bone Disease)

Abstract: Gorham-Stout syndrome, or disappearing bone disease, is characterized by the proliferation of thin-walled vascular channels associated with regional osteolysis. There have been fewer than 150 cases reported in the literature. In this clinical report, we describe 2 additional cases of Gorham-Stout syndrome affecting the maxillofacial skeleton. We provide a review of the clinical diagnosis of this syndrome and describe treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 15 publications
1
16
0
2
Order By: Relevance
“…Ethology is not clear. Osteolysis secondary to angiomatosis [9], increased osteoclast activity due to high level of IL6 [2] and minor traumas are accused [1]. Our patient gave a history of minor trauma in childhood.…”
Section: Discussionmentioning
confidence: 74%
“…Ethology is not clear. Osteolysis secondary to angiomatosis [9], increased osteoclast activity due to high level of IL6 [2] and minor traumas are accused [1]. Our patient gave a history of minor trauma in childhood.…”
Section: Discussionmentioning
confidence: 74%
“…However, other authors have found osteoclasts in the affected tissue, suggesting that bone resorption is caused by increased osteoclast activity [10] and is mediated by stimulating cytokines such as interleukin-6 [11]. Although the etiology is unknown, up to 50% of the cases are associated with previous trauma [12]. This disease usually affects young people without predilection for sex, race or genetic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…As a general rule, the persons that suffer from the disease are younger than 40-year-old [16] , while an epidemiologic correlation with race, gender and geography does not seem to exist [9,[17][18][19] . However, some authors noticed a clear "predilection" of the disease in males [20] .…”
Section: Clinical Featuresmentioning
confidence: 99%